Certain Subordination Properties for Subclasses of Analytic Functions Involving Complex Order - S. Sivasubramanian; Aabed Mohammed; Maslina Darus (Abstract and Applied Analysis)
We derive several subordination results for a certain class of analytic functions defined by the Sălăgean operator In the present investigation.